KAJIAN TINGKAT PELAYANAN JALAN (LOS) AKIBAT HAMBATAN SAMPING DI JALAN UTAMA PERUMAHAN TLOGOSARI SEMARANG - Ummi Marshush (Universitas Bina Taruna Gorontalo, 2023)
Land is an important requirement for the life of living things, especially for humans. Increasing the new land use due to resident activities will fill the empty space and shift existing activities resulting in changes in land use. Bumi Tlogosari housing is one of the housing areas in Pedurungan District, Semarang City, which has now developed into a densely populated housing area. The high population then causes an increase in activities carried out in housing. The existence of trading activities as a road side obstacle actually has an impact on the level of service (LOS). Analysis of road service levels resulted in criteria A, B and C. In the morning both roads are classified as classification A (Current Flow, Low Volume, High Speed). In the afternoon on Jalan Tlogosari 1 classified as C classification (Stable Flow, Speed influenced by traffic, Suitable Volume) and B classification (Stable Flow, Limited Speed, Suitable Volume) on Jalan Tlogosari Raya 2.